Pathological complete response after monotherapy with immune checkpoint inhibitors for bifocal colon cancer in a patient with lynch syndrome and situs inversus totalis: a case report - Feng, Jun; Niu, Wenbo; Zhang, Juan; Ding, Yuanyi; Li, Zheng; Zhang, Jianfeng; Li, Baokun; Li, Chenhui; Wang, Feifei; Wang, Guiying; Yu, Bin (Frontiers in Immunology, 2025)
BackgroundLynch syndrome is the most common hereditary colorectal cancer (CRC) syndrome, accounting for 3–5% of all CRC cases. Situs inversus totalis (SIT) is a rare congenital malformation with an incidence of 1 in 8,000 to 1 in 25,000. The co-occurrence of Lynch syndrome and SIT is extremely uncommon. Immune checkpoint inhibitors (ICIs) have demonstrated significant efficacy in treating microsatellite instability-high/deficient mismatch repair (MSI-H/dMMR) CRC. Tumors associated with Lynch syndrome frequently exhibit MSI-H, providing a theoretical basis for ICI use.Case presentationWe report a case of bifocal colon cancer associated with Lynch syndrome and SIT. After seven cycles of sintilimab, the patient developed gastrointestinal perforation due to tumor regression, necessitating emergency surgery. The anatomical variations associated with SIT required the surgical team to adopt an alternative approach. Postoperatively, the patient continued sintilimab treatment for 2 years. In June 2024, he underwent a colostomy reversal and proximal colectomy. Pathological examination revealed a tumor regression grade (TRG) of 0, indicating complete pathological remission (pCR), with no recurrence or metastasis detected upon follow-up.ConclusionsThe anatomical variations associated with SIT increase the complexity of surgical procedures. Advanced imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) are essential for assessing fine anatomical details and facilitating surgery. ICIs are an effective treatment option for Lynch syndrome-associated CRC, as demonstrated in this case. Future studies should investigate the optimal timing of immunotherapy, combination treatment strategies, and methods to mitigate immune-related toxicities. Such research will help develop comprehensive and personalized treatment plans for Lynch syndrome-associated CRC.